Demonstration of anaerobic membrane bioreactors for resource recovery in wastewater treatment applications. - Paissoni, Eleonora (Cranfield University, 2023)
Pilot-scale studies on anaerobic membrane bioreactors (AnMBRs) for municipal wastewater treatment at low temperature (<20°C) showed promising results, however, their application at larger scale is still relatively unknown. This study investigated the scalability of an AnMBR, comprising an upflow anaerobic sludge blanket (UASB) reactor and an external ultrafiltration membrane tank, operating AnMBRs both at pilot- and demonstration-scale and identifying how sludge physical and microbiological properties, membrane design and variations in influent temperature, chemical oxygen demand (COD) and sulphate (SO₄) influence the successful scale-up of the technology. At pilot-scale, the source and adaptation of the inoculum and the orientation and arrangement of the membrane fibres did not affect the performance of the reactors. However, the use of horizontal hollow fibres led to lower gas sparging energy consumption compared to a vertical module. The membrane improved removal efficiencies (from 49-57% to 88-92% COD removal), solids hydrolysed (from 0.82-0.86 g/(L∙d) to 1.57-1.87 g/(L∙d)) and methane production (from 2.3-2.7 L/d to 5.3-5.7 L/d). Methanogenesis percentages were linearly correlated to hydrolysis, which in turn was affected by temperature and inversely correlated to the Sauter mean diameter of the sludge particles. Higher substrate affinities were found at the operational temperature of the reactors (15-20°C), while hydrolytic enzyme activities in UASB reactors and AnMBRs were higher at 37°C. Methane was mainly dissolved in the effluent (70-90%), implying the need for a recovery process to improve the net energy balance. At demonstration-scale, low COD:SO4 ratio caused competition between sulphate-reducing bacteria and methanogens, leading to a decrease in methane yield. This study proved that AnMBRs are a suitable technology to treat municipal wastewater, however site- specific control strategies to manage fouling and sulphate and appropriate post- treatments are necessary to ensure the successful application of the process at full-scale in temperate climates and the recovery of useful resources from wastewater.
Jefferson, Bruce - Associate Supervisor
Keywords: demonstration-scale; dissolved methane; fouling; hollow-fibre; horizontally orientated membrane module; hydrolysis; hydrolytic enzyme activity; inoculum; low temperature; methane; municipal wastewater; pilot-scale; scalability; substrate affinity; sulphate-reducing bacteria; UASB; upflow anaerobic sludge blanket reactor